(Cost)effectiveness of life review for Older Adults: Design of a randomized controlled trial - Onrust Simone; Melenhorst Anne-Sophie; Pot Anne; Bohlmeijer Ernst T (BMC, 2008)
Abstract Background Depression in older adults is a serious health problem with a poor prognosis. There is a need for indicated preventive psychological interventions for older adults, that show to be promising in preventing depressive disorders. Methods/design This manuscript describes the design of a study evaluating 'Looking for Meaning', a newly developed prevention course for older adults with depressive symptoms, based on life-review. Both clinical and economic effectiveness are evaluated in a pragmatic randomized controlled trial. The control condition of this 12-session preventive intervention is a 20-minute video movie. The primary outcome is symptoms of depression at post-treatment and follow-up (6 months after post-treatment). Secondary outcomes are symptoms of anxiety, satisfaction with life, mastery, reminiscence styles, quality of life, and health care costs. An additional result of this study is the insight into the working elements of the course, provided by the qualitative study. The qualitative data, mainly based on 20 open-ended interviews with participants, are to be analyzed with an emphasis on newly emerging insight. Discussion This study will add to the existing scientific knowledge in several ways, especially by also including an economic evaluation and a qualitative study to gain insight into the working mechanisms of the course, both rather new in the field of life review. Positive results of this study will make an evidence-based intervention to improve public health among older people available. Trial registration Current Controlled Trials Ltd, ISRCTN66645855